Analysis of Financial Performance Using Budget Absorption Indicators - Safriansah Safriansah; Nizwan Zukhri; Andriyansah Andriyansah (Budapest International Research and Critics University, 2021)
Budget absorption is one indicator in measuring the performance of the state revenue and expenditure budget. Most of the budget realization occurred in the fourth quarter. The absorption of the budget, especially expenditure on goods and services, has a significant effect in driving economic growth. The research objective was to analyze the effect of budget planning, budget execution, government internal control systems on budget absorption, financial performance at the